Benefits of the wholesale only model for fibre deployment in Italy - Ilsa Godlovitch; Julian Knips; Christian Wernick (WIK-Consult GmbH, 2020)
The wholesale only business model, in which fiber connections are only marketed at the wholesale level and not directly to end customers, is widespread in many European countries and is structurally different from vertically integrated models. In Italy, the wholesale only provider Open Fiber is the main driver of fiber network expansion with over 9.5 million connected premises, including over three million households in rural areas. On behalf of Open Fiber, WIK has examined this business model more closely in a dedicated report. The increased penetration of fiber connections in Italy not only helps to spread smart city applications, but also offers potential for saving greenhouse gases compared to copper-based connections. From an investor's point of view, infrastructure investment in wholesale only networks is attractive because they provide relatively stable long-term returns. These networks offer potential advantages for wholesale customers, as the risk of discrimination is smaller in comparison to vertically integrated wholesale supplier. Finally, retail customers benefit from the choice between different ISPs. – – Das Wholesale-only-Geschäftsmodell, bei dem Glasfaseranschlüsse nur auf der Wholesale-Ebene und nicht direkt an Endkunden vermarktet werden, ist in vielen europäischen Ländern verbreitet und unterscheidet sich strukturell von vertikal integrierten Modellen. In Italien ist der Wholesale-only-Anbieter Open Fiber der Haupttreiber des Glasfaserausbaus mit über 9,5 Millionen angeschlossenen Standorten, davon über drei Millionen Haushalte in ländlichen Gebieten. Im Auftrag von Open Fiber hat das WIK dieses Geschäftsmodells in einer Studie näher beleuchtet. Die erhöhte Verbreitung von Glasfaseranschlüssen in Italien hilft nicht nur bei der Verbreitung von Anwendungen im Smart-City-Bereich, sondern bieten auch Potenzial für das Einsparen von Treibhausgasen im Vergleich zu Anschlüssen auf Kupferbasis. Aus Investorensicht ist ein Infrastrukturinvestment in Wholesale-only-Netze attraktiv, da diese langfristig stabile Renditen liefern. Für Zugangsnachfrager bieten diese Netze potenziell Vorteile, da ein geringeres Diskriminierungsrisiko als bei vertikal-integrierten Vorleistungsanbietern besteht. Endkunden profitieren schließlich von den Wahlmöglichkeiten zwischen verschiedenen ISPs.
Additional information: Study for Open Fiber
Keywords: 330